1996
DOI: 10.1007/bf02246454
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and bioavailability of midazolam after intravenous, subcutaneous, intraperitoneal and oral administration under a chronic food-limited regimen: relating DRL performance to pharmacokinetics

Abstract: The effects of midazolam on animal behavior often are evaluated under a chronically food-limited regimen, which is used to implement food-reinforced performance, but the corresponding pharmacokinetics are lacking. The present study investigated the pharmacokinetics of midazolam after i.v., s.c., i.p., and p.o. administration in food-limited rates. A two-compartment model best described the concentration-time profiles for the four routes of administration. The rate of midazolam absorption was rapid, and peak co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…Consistent with previous studies (Mandema and Danhof, 1992;Lau et al, 1996;Higashikawa et al, 1999a,b,c;Laurijssens and Greenblatt, 2002), clearance of intravenously administered midazolam in rats was high, with a mean control clearance value (without inhibitor) of 79 ml/min/kg. Intragastric midazolam had a mean net bioavailability of only 11%.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous studies (Mandema and Danhof, 1992;Lau et al, 1996;Higashikawa et al, 1999a,b,c;Laurijssens and Greenblatt, 2002), clearance of intravenously administered midazolam in rats was high, with a mean control clearance value (without inhibitor) of 79 ml/min/kg. Intragastric midazolam had a mean net bioavailability of only 11%.…”
Section: Discussionsupporting
confidence: 90%
“…28 Oral dosing of KTZ was chosen to maximize KTZ liver uptake, wherein the drug would first pass through the liver during entry to the systemic circulation. The study design also matched well with other experimental designs previously reported in literature having an average time interval between the two doses ranging from 0.5 to 2 h. [28][29][30][31] The CL of MDZ in NL rats (Table 1) was similar to previous reports, [29][30][31][32] although the t 1 2 appeared to be longer. The underlying reason behind may be that in the current study, MDZ was measured for up to 8 h after i.v.…”
Section: Discussionsupporting
confidence: 75%
“…Starvation is known to affect microsomal enzymes (Ma et al 1989) and thereby alter the bioavailability of hexobarbital (Sachan 1982), midazolam (Lau et al 1996) and other drugs (Ma et al 1989). Food restriction may also increase CNS entry of AG and metabolites by opening the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 98%